Hadith #1935 - Sunan Ibn Majah - al-Dahhak bin Mazaham الضحاك بن مزاحم الهلالي; Anas ibn Malik; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Kathir bin Slym al-Dby كثير بن سليم الضبي (Sunan Ibn Majah)
“Prices rose at the time of the Messenger of Allah (ﷺ), and they said: ‘Why do you not fix the food prices, O Messenger of Allah?’ He said: ‘I hope that when I leave you, no one among you will be demanding restitution for a wrong that I have done to him.”‘
Grade:

Hadith #3382 - Sunan Ibn Majah - Anas ibn Malik; Jabbarh bin al-Mghls al-Hmany Abu جبارة بن المغلس; Kathir bin Slym al-Dby كثير بن سليم الضبي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade me to wear a ring on this and on this,” meaning the little finger and the thumb.
Grade:

Hadith #3433 - Sunan Ibn Majah - Anas ibn Malik; Jabbarh bin al-Mghls al-Hmany Abu جبارة بن المغلس; Kathir bin Slym al-Dby كثير بن سليم الضبي (Sunan Ibn Majah)
“I am riding to the Jews tomorrow. Do not initiate the greeting with them, and if they greet you, then say: Wa ‘alaikum (and also upon you)”.
Grade:

Hadith #3479 - Sunan Ibn Majah - Anas ibn Malik; Jabbarh bin al-Mghls al-Hmany Abu جبارة بن المغلس; Kathir bin Slym al-Dby كثير بن سليم الضبي (Sunan Ibn Majah)
“One who is consulted is entrusted.”
Grade:

Hadith #3606 - Sunan Ibn Majah - Anas ibn Malik; Jabbarh bin al-Mghls al-Hmany Abu جبارة بن المغلس; Kathir bin Slym al-Dby كثير بن سليم الضبي (Sunan Ibn Majah)
his father said: “The Messenger of Allah (saas) said: Allahumma Anta Rabbi la ilaha illa Anta, khalaqtani wa ana ‘abduka wa ana ‘ala ‘ahdika wa wa’dika mastata’tu. A’udhu bika min sharri ma sana’tu, abu’u bi ni’matika wa abu’u bi dhanbi faghfirli, fa innahu la yaghfirudh-dhunuba illa Anta (O Allah, You are my Lord, there is none worthy of worship except You. You have created me and I am Your slave, and I am adhering to Your covenant and Your promise as much as I can. I seek
Grade: